1988
DOI: 10.3758/bf03197752
|View full text |Cite
|
Sign up to set email alerts
|

Short-term memory for Chinese characters and radicals

Abstract: Short-term memory for Chinese radicals and characters, varying in orthographic complexity, frequency, and-for radicals-intercharacter frequency (the number of compound characters that contain the radical), was studied using an immediate free-recall task. When radicals or characters are relatively frequent, so that their pronunciations are well known by literate Chinese, they seem to be maintained in verbal form in short-term memory. For these stimuli, intercharacter frequency and complexity have relatively sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
2
10

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 26 publications
3
29
2
10
Order By: Relevance
“…The results of this study further confirm the finding of previous studies that sensitivity of STM to phonological similarity is not a function of the nature of the writing system for the language being tested (Erickson et al, 1977;Hue & Erickson, 1988;Ren & Mattingly, in press;Tzeng et al, 1977;Yik, 1978;Zhang & Simon, 1985). The findings of this study also add a new aspect of the phonology, namely, tonal features in tone languages, to the list of the feature classes to which STM is sensitive.…”
Section: Discussionsupporting
confidence: 79%
“…The results of this study further confirm the finding of previous studies that sensitivity of STM to phonological similarity is not a function of the nature of the writing system for the language being tested (Erickson et al, 1977;Hue & Erickson, 1988;Ren & Mattingly, in press;Tzeng et al, 1977;Yik, 1978;Zhang & Simon, 1985). The findings of this study also add a new aspect of the phonology, namely, tonal features in tone languages, to the list of the feature classes to which STM is sensitive.…”
Section: Discussionsupporting
confidence: 79%
“…However, there have also been some findings indicating visual similarity effects in serial and free recall (Avons & Mason, 1999;Hue & Erickson, 1988;Logie, Della Sala, Wynn, & Baddeley, 2000;Smyth, Hay, Hitch & Horton, 2003;Walker, Hitch, & Duroe, 1993) indicative of at least some involvement of a visual memory system in these tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical techniques including the effects of visual similarity have suggested that visual structure is maintained in the visuo-spatial sketchpad (Hue & Ericsson, 1988;Logie, Della Sala, Wynn & Baddeley, 2000). The use of irrelevant pictures has suggested that perceived inputs have direct and obligatory access to the system, causing detrimental effects on short-term recall and recognition for visuo-spatial material, analogous to the irrelevant speech effect on the phonological loop (Logie, 1986;Logie & Marchetti, 1991;Toms, Morris, & Foley, 1994).…”
mentioning
confidence: 99%